FoxA1 is a Key Mediator of Hormonal Response in Breast and Prostate Cancer - Robinson, Jessica; Carroll, Jason (Frontiers in Endocrinology, 2012)
Hormonally regulated breast and prostate cancers are the most common cause of cancer in females and males respectively. FoxA1 acts as a pioneer factor for both androgen receptor (AR) and estrogen receptor-α (ER), dictating the binding location, and therefore function of these transcription factors. It is an essential protein for the transcriptional activity of both ER and AR, yet it has distinct roles with the two different nuclear receptors. In both malignancies, FoxA1 plays a pivotal role from early stage cancer through to drug resistant and metastatic disease. Due to this key role in mediating ER and AR function, FoxA1 is not only an attractive therapeutic target but could potentially function as a novel biomarker.